Intelligent quantitative assessment on the spray performance of alternative aviation fuel - Liu, Ziyu; Wang, Zhichao; Gu, Xiaoyu; Liu, Haobo; Yang, Luhua; Yang, Jingying; Yang, Xiaoyi (Frontiers in Energy Research, 2022)
Drop-in alternative aviation fuel (AAF), as a blend of petroleum-derived kerosene with sustainable jet fuel, has the advantage in CO2 reduction and could be used without any modifications to the engine and aircraft. Therefore, drop-in AAF blending could not scarify the performance compared to traditional jet fuel. For assessing the spray performance quantitatively, traditional jet fuel (RP-3) with blending alternative compositions including paraffins, cycloparaffins, and aromatics was designed. Carbon number distribution and classification distribution in jet fuel compositions that would influence spray performance are well investigated. The cone angle and liquid length are recognized by a shadow image, while Sauter mean diameter (SMD) and velocity are investigated by phase-Doppler anemometry (PDA). The liquid length and droplet size of bicyclohexane, phenyl-cyclohexane, heptadecane, and octadecane conduct a significant deviation compared with RP-3, which complies with the large deviations of Lb (f)[σ0.25 μf0.25 ρf0.25], which extracted the fuel property item from the liquid length, and Oh(f) [μfσ−0.5ρf−0.5], which extracted the fuel property item from the Ohnesorge number. The blending fuels of those cannot be certified as drop-in fuel due to obvious deviation to RP-3, which also presents differences in carbon number distribution and classification distribution. The spray empirical models were established quantitatively to assess the characteristics of the liquid sheet and droplet for discovering the blend fuel effects. The empirical equations of the liquid length and SMD calibrated by evaporation constants can agree well with the experimental data except for blends of bicyclohexane, phenyl-cyclohexane, C17, and C18. The integrated spray performance assessment models developed could benefit from certifying drop-in fuel at the spray level quantitatively.